Hubungan Quarter Life Crisis dengan Tingkat Harga Diri pada Mahasiswa Fakultas Ilmu Kesehatan Universitas Muhammadiyah Jember - Pratama, Rizki Ghifari (Mando Care Jurnal, 2025)
Quarter life crisis (QLC) is a developmental crisis phase in early adulthood characterized by anxiety, confusion about life direction, and social pressures, all of which can contribute to low self-esteem. Students of the Faculty of Health Sciences at Muhammadiyah University of Jember are also not exempt from this phenomenon, which may impact their psychosocial and academic well-being. This study employed a quantitative design with a cross-sectional approach to analyze the relationship between QLC and the risk of low self-esteem among these students. The study population comprised all active students totaling 553 individuals, with a sample of 232 respondents selected using purposive sampling. Data were collected using the Quarter Life Crisis Scale and Rosenberg Self Esteem Scale questionnaires, and analyzed with the Spearman Rank (Rho) test at a significance level of α = 0.05. The study revealed that most students were in the low QLC category (46%) and had moderate levels of low self-esteem risk (65%). There was a tendency for higher levels of QLC to be associated with higher risks of low self-esteem. The Spearman test showed p = 0.000 (<0.05) with a correlation coefficient of r = 0.523, indicating a significant, strong, and positive relationship between QLC and the risk of low self-esteem. There is a significant relationship between quarter life crisis and the risk of low self-esteem among students of the Faculty of Health Sciences at Muhammadiyah University of Jember. The findings of this study recommend strengthening the role of academic advisors in providing psychosocial support, as well as encouraging active parental involvement through open communication and emotional support to help students cope with Quarter Life Crisis and prevent the risk of low self-esteem.